The intrinsic impact of mechanical stress on the maintenance of oocyte dormancy - Go Nagamatsu; Kenjiro Shirane; Yuzuru Kato; Hiroko Nakamura; Norio Hamada; Kiyoko Kato; Hiroshi Kimura; Katsuhiko Hayashi (Proceedings of the National Academy of Sciences, 2026)
In the mammalian ovary, most oocytes remain dormant, and their dormant status plays a central role in maintaining the reservoir population of the female germ line. The equilibrium between the dormant and active states, the latter of which is responsible for producing mature oocytes, is therefore crucial for ensuring the sustained reproductive capability of females. We have previously reported that mechanical stress in the ovary plays a crucial role in oocyte dormancy. However, the mechanism underlying this relation remains unclear. Here, we demonstrated that the mechanical stress is directly transduced into the oocytes, rather than to the surrounding granulosa cells. Culture experiments and live-imaging analysis revealed the nuclear localization of FOXO3, a hallmark of oocyte dormancy, within oocytes cultured alone in response to mechanical stress. Interestingly, we found that the cytological response to mechanical stress was accompanied by ligand-independent internalization of the c-kit receptor, which dampens intracellular signaling and prevents oocyte activation. These results shed light on the relation between mechanical stress and oocyte dormancy and provide clues toward a greater understanding of female reproductive capability.